Investigating factors influencing inrention to use e-management in oil and gas industry in Libya - Bashir R B Abuzwida (Universiti Sains Islam Malaysia, 2024)
Libya is one of the most prominent oil and gas producing countries in the world. The country, however, needs to embrace new technologies in order to be able to maintain its production levels. It faces various developmental obstacles such as operational impediments, limited operational expertise, strategic planning and ineffective implementation of information technology. Therefore, the main objective of this study was to focus on identifying the level of beliefs and identified decisions of users towards the acceptance of e-management in oil and gas industry. Based on the UTAUT framework, this study investigates the extent to which the behavioural factors (performance expectancy, effort expectancy, social influence, and facilitating conditions) improve behavioural intention of managers working in selected government oil companies of Libya. Besides, in this study, perceived credibility is added as an independent variable that theoretically extends the current model. Structural equation modelling was used to examine the exploratory and confirmatory factor analysis of the instruments. Confirmatory factor analysis were utilised to test the hypotheses postulated in the study. All the hypotheses were accepted. The finding of the research confirms that effort expectancy is an important factor that increases behavioural intention of the employees. From the four attributes of behavioural factors, effort expectancy and perceived credibility are very important for the increase behavioural intention of the managers in the organisation to use e-management technology. The findings also confirm that perceived information quality boosts the actual usage of e-management in the Libyan oil and gas sector. If the information is misinterpreted, the trust on the system by the users will reduce, which likely will lead to not use the system. Thus, the quality of the information is very crucial especially in the oil and gas sector. Therefore, in order to enhance usage of e-management in the employee context, perceived information quality and perceived credibility are believed to influence intention more than that of information system practices. The modified UTAUT framework provide insights for managers and practitioners to increase the supply of increase information disclosure along with increased one’s employability and contributes significantly towards the theoretical enhancement and body of knowledge. Furthermore, this study has attempted to provide practical contribution to practitioners who implement e-management in Libya such as top managers, policy makers, IT officers, performance managers, human resource specialist and strategists; who can benefit from a better understanding of this issue. It will particularly help managers and strategists to focus on new possibilities of improving e-environment in Libya. The findings from this research will also help the oil industry in Libya to form strategies to support e-management applications in order to enhance efficiency and effectiveness of their management tools. The findings also reveal that managers’ performance expectancy and social influence and perceived credibility may significantly predict the overall usage of e-management. Finally, this study suggests that additional communication skills need to be demonstrated in order to improve the overall acceptance level of e-management.